KORELASI UKURAN MORFOMETRIK DENGAN BOBOT BADAN PADA DOMBA EKOR TIPIS BETINA DARA DI KABUPATEN SEMARANG, JAWA TENGAH - Hasna Fajar Suryani; Muhammad Hilmi Mustofa; Nadlirotun Luthfi (Wahana Peternakan, 2023)
The aims of this study were to identify the morphometric measurements and body weights of Thin-tailed ewe, examine the qualitative characteristics of ewe and examine the close relationship between body weight and other body measurements. This study used 40 female Thin-tailed Ewe aged under 1 year. The method used was purposive sampling. Parameters observed were face length, ear length, chest circumference, chest width, chest depth, body length, shoulder height, hip height, hip width, front leg length, hind leg length, tail length and body weight. Data were analyzed using correlation and simple linear regression analysis. The results showed that the qualitative characteristics of Thin-Tailed ewes were small body shape, white fur color with black spots around the eyes, nose and other body parts. The morphometric measurements most closely related to body weight were chest width and chest circumference. Based on the result, it can be concluded that the determination value in the chest, the equation from chest determination can be used to predict body weight of Thin-Tailed ewe. the equation of y = 1.2118x - 10.532 means that every 9.52 cm increase in the chest will be accompanied by an increase in body weight of 1 kg.   Keywords: Body Weight, Ewe, Morphometric